Association Between Expected Goals (xG) and Goal Scoring Across Club and National Team Competitions in Elite Football - Cristian Murillo García (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study: The purpose of this study was to analyze the association between xG and goals scored in soccer matches. Materials and methods: This study was quantitative, correlational, and longitudinal. 333 league matches were analyzed. The dataset was obtained from Sofascore, a website that offers statistics and results from various sporting events. The hypothesis was put forward that there is a positive correlation between xG and goals scored. The sample consisted of 333 official matches from international competitions, including the 2013/24 Champions League, the 2024 Copa Libertadores, Euro 2024, and the 2024 Copa América. These tournaments were selected due to their significant international relevance. Results: The results of this research confirm the validity of using xG as an indicator for analyzing a team's offensive performance, although its predictive capacity tends to vary depending on the context or competition. In clubs, players have more continuity because they train together, which makes it easier to establish a playing pattern, so this may be a reason for higher xG compared to national team tournaments. Conclusions: The results obtained in this study confirm the relationship between xG and goals scored in football matches, thus establishing it as a valid indicator for measuring offensive performance in football. It was found that in club tournaments, the amount of association, in the Copa Libertadores (r = 0.537) having the best association between the variables, in the Champions League the association was lower (r = 0.403). Meanwhile, in national team tournaments, the values ​​for the Copa América and Euro were (r = 0.475) and (r = 0.479), respectively, where some similarity can be observed in the association of variables, which is attributed to the poor group cohesion and poor tactical fit of the national teams compared to the clubs.